Geometria dinâmica e o cálculo diferencial e integral - Paranhos, Marcos de Miranda (2009)
The aim of this work is to present fundamental ideas of differential and integral calculus and its applications in solving problems. As a teacher of calculus, I see my trajectory and by exchanging experiences with other professionals, a common sense about the mechanization of techniques and low student achievement in relation to the ideas and applications so significant that the calculation might provide. Reflecting, experiencing and informing me about this issue, I think much of this problem in a limited way with which we have presented these ideas in our classes. Every teacher develops along its trajectory ways to represent the ideas you want to convey and that is the essence of pedagogical reasoning. In that sense, I understood that every idea must be transformed to be taught and it was this aspect that directed this work. Inspired by the possibility of using software in the teaching of Mathematics and didactically based on "Dialectic Tool-Object" and "Game Tables" by Régine Douady, I performed this work that consists of a sequence of activities, divided into six modules, where basic ideas about derivative, integral and optimization functions are presented by means of software and GeoGebra Winplot. The strings are made to functions with one and two variables, can be developed along with the student or be provided only by the teacher. I hope with this work is expanding the size that most students have the Calculus and its applications, besides stimulating the use of technological resources as tools for large capacity in interpreting and solving problems